Serial Verb Constructions in North-West Semitic languages: From a synchronic radiation back to the ‘Big Bang’ - Andrason, Alexander (Stellenbosch Papers in Linguistics Plus, 2022)
The present article argues that Serial Verb Constructions (SVCs) in North-West Semitic (NWS) languages have emerged from clause fusion. The analysis of the synchronic profiles of SVCs in four of the oldest attested languages of this branch, i.e., Canaano-Akkadian, Ugaritic, Biblical Hebrew, and Biblical Aramaic, reveals an evolutionary path from less cohesive non-canonical serializing patterns of a pseudo-coordinated character to increasingly more cohesive and canonical serializing patterns. The ultimate source of this path and verbal serialization is reconstructed as conjunctive coordination with two clauses being linked by the predecessor of a coordinator that surfaces as u/w in the four analyzed languages.